Success Factors and the Adoption of E-Government in Jinja District Local Government, Uganda - Mugavu, George (Kabale University, 2025)
The Purpose of this study was to examine the success factors influencing the adoption of e-government in Jinja District Local Government, Uganda. The research sought to identify the roles of political, financial, institutional, and technological factors in facilitating e-government adoption. Interms of methodology the study was purely guided by two research designs that was to say the cross-sectional research design and the casestudy research design. The study adopted a pragmatic research philosophy integrating both deductive and inductive approaches. A mixed-methods framework combining cross-sectional survey and case study designs was employed. Data were collected from a sample of 200 respondents using structured questionnaires and interview guides, achieving an 89% response rate. Data Analysis: Quantitative data were analyzed using descriptive statistics and linear regression, while qualitative data were subjected to thematic analysis. Findings revealed that e-government adoption is significantly associated with political will (r=.254, p<0.001), budgetary allocation (r=.337, p<0.001), enabling environment (r=.177, p<0.023), citizen motivation (r=.213, p<0.005), and public sector reforms (r=.210, p<0.005). Training-related factors, including software (r=.694, p<0.001), hardware (r=.679, p<0.001), and data security training (r=.553, p<0.0001), also demonstrated strong positive associations. Furthermore, technological infrastructure such as network availability (r=.665, p<0.000), video conferencing (r=.562, p<0.000), and reliable energy supply (r=.655, p<0.000) significantly influenced adoption. Thematic findings underscored the critical role of continuous employee training, budgetary commitment, and reliable ICT infrastructure in the success of e-government initiatives. Limitations of the Study: The study was limited to one district, which may constrain the generalizability of findings across other regions of Uganda. Additionally, reliance on self-reported data may have introduced response bias. Research Contributions: The study contributes empirical evidence on the determinants of e-government adoption in local government contexts of developing countries. It provides practical insights for policymakers and administrators to enhance ICT capacity, institutional readiness, and infrastructure for improved service delivery.